2021
DOI: 10.3389/fonc.2021.616740
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Radiomics Analysis of 1p/19q Status in WHO Grade II Gliomas

Abstract: PurposeThe present study aimed to preoperatively predict the status of 1p/19q based on radiomics analysis in patients with World Health Organization (WHO) grade II gliomas.MethodsThis retrospective study enrolled 157 patients with WHO grade II gliomas (76 patients with astrocytomas with mutant IDH, 16 patients with astrocytomas with wild-type IDH, and 65 patients with oligodendrogliomas with mutant IDH and 1p/19q codeletion). Radiomic features were extracted from magnetic resonance images, including T1-weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have shown that astrocytomas and oligodendrogliomas exhibit heterogeneous radiomic features, and machine learning can significantly improve the identification of the 2 tumors. 33–35 In our research, we used 6 radiomic features to establish a prediction model, we found that the established model with the AUC, accuracy, sensitivity, and specificity were 0.845/0.800, 0.767/0.731, 0.712/0.789, and 0.817/0.676 in the training set and validation set, respectively. Each of these 6 features represents a texture feature of the image, this is consistent with the phenomenon that oligodendrogliomas and astrocytomas exhibit different signal uniformity on T2WI.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have shown that astrocytomas and oligodendrogliomas exhibit heterogeneous radiomic features, and machine learning can significantly improve the identification of the 2 tumors. 33–35 In our research, we used 6 radiomic features to establish a prediction model, we found that the established model with the AUC, accuracy, sensitivity, and specificity were 0.845/0.800, 0.767/0.731, 0.712/0.789, and 0.817/0.676 in the training set and validation set, respectively. Each of these 6 features represents a texture feature of the image, this is consistent with the phenomenon that oligodendrogliomas and astrocytomas exhibit different signal uniformity on T2WI.…”
Section: Discussionmentioning
confidence: 84%
“…The sample size ranged from 42 to 1748. Most studies focused on WHO 2–4 glioma or WHO 2–3, with one study including only WHO 2 glioma 24 and one study including only WHO 4 glioma 25 . For the target condition, 10 studies focused on IDH mutation combined 1p/19q co‐deletion, while 18 studies on 1p/19q co‐deletion only.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating studies have successfully predicted the status of IDH , 1p/19q codeletion, and TERT mutation by using AI models. [ 39 , 40 ] The increasing accuracy of these predictive models has brought them close to being used in clinical diagnosis, and enlarging the sample size and improving their advanced algorithms have the potential to further improve the accuracy and robustness of these models. We believe that validation of these predictive models through prospective clinical trials will make the use of molecular features for guiding tumor resection a reality in the near future.…”
Section: Clinical Implications Of Molecular Pathology In the Therapy ...mentioning
confidence: 99%
“…Fortunately, with the development of artificial intelligence (AI) and radiomics, predicting the molecular features of gliomas through models based on radiomic characteristics is a hopeful potential. Accumulating studies have successfully predicted the status of IDH , 1p/19q codeletion, and TERT mutation by using AI models [39,40] . The increasing accuracy of these predictive models has brought them close to being used in clinical diagnosis, and enlarging the sample size and improving their advanced algorithms have the potential to further improve the accuracy and robustness of these models.…”
Section: Clinical Implications Of Molecular Pathology In the Therapy ...mentioning
confidence: 99%